Single-port laparoscopic appendectomy for acute appendicitis during pregnancy - Cho, In Soo (J Minim Access Surg, 2021)
AIM OF STUDY: Acute appendicitis is the most common non-obstetric surgical problem in pregnant patients. As minimally invasive surgery has developed, minimising surgical trauma and improving cosmetic outcomes have led to the development of single-port laparoscopic surgery (SPLS). The aim of this study was to assess the feasibility and safety of SPLS for acute appendicitis during pregnancy. PATIENTS AND METHODS: Between September 2014 and May 2016, 12 pregnant patients diagnosed with acute appendicitis and having single-port laparoscopic appendectomy were included in the study. RESULTS: The median gestational age at surgery was 16 weeks (6–30 weeks). All operations were completed safely and without vascular or visceral injury. Four patients (33.3%) required conversion to a reduced-port laparoscopic surgery with 3 patients (25%) having a 5 mm port inserted because of perforated appendicitis with drain placement, and 1 patient (8.3%) having a 2-mm needle instrument insertion. Median operation time was 60 min (32–100 min), and a drainage tube was placed in 5 patients (41.7%). Median total length of incision was 2 cm (1.2–2.5 cm). The median time to soft diet initiation and length of stay in the hospital were 1 day (0–9 days) and 5 days (2–11 days), respectively. Two patients (8.0%) developed post-operative complications: One wound site bleeding and two surgical site infections. One case of abortion (8.3%) was noted on the post-operative day 1 and one case of imperforate hymen was noted after delivery. CONCLUSIONS: SPLS appendectomy is feasible and safe for treating patients with acute appendicitis during pregnancy.